Effects of anisotropic exchange on the micromagnetic domain structures - Schaadt, D; Engel-Herbert, R; Hesjedal, T (2007)
We have investigated the influence of anisotropic exchange on the micromagnetic domain structure. Three-dimensional simulations based on the Landau-Lifshitz-Gilbert equation were performed incorporating a generalized tensor representation of the exchange following a phenomenological approach. In comparison to isotropic exchange, which is usually used in micromagnetic simulations, anisotropic exchange significantly affected the equilibrium distribution of the magnetization. The formation of slanted domain walls aligning in the direction of stiffest exchange and the deformation of edge domains were the most prominent consequences. In general, we found that anisotropic exchange may have profound effects on magnetic nanostructures. © 2007 WILEY-VCH Verlag GmbH and Co. KGaA.